Groundwater hydrology - Todd, David Keith, 1923- (Wiley, 2005)
Introduction -- Occurrence of groundwater -- Groundwater movement -- Groundwater and well hydraulics -- Water wells -- Groundwater levels and environmental influences -- Quality of groundwater -- Pollution of groundwater -- Groundwater flow modeling techniques -- Management of groundwater -- Surface investigations of groundwater -- Subsurface investigations of groundwater -- Artificial recharge of groundwater -- Saline water intrusion in aquifers.